Advancing Gender's Balance Rights Through Constitutional and Legal Reforms: A Comparative Study of Nigeria and Uganda - Aidonojie, Paul Atagamen; Izevbuwa, Osaretin George; Obieshi, Eregbuonye; Okpoko, Mercy; Damina, Joshua John (Journal of Indonesian Constitutional Law, 2025)
The concept of human rights has gained global recognition over time, and the international community and virtually all countries consider everyone equal and deserving of equal treatment. However, advancing gender balance in rights is a critical challenge in Nigeria, where constitutional and legal frameworks come short of equity. Hence, the study focuses on Nigeria's slow progress in addressing systemic gender imbalances that are further complicated by cultural and institutional barriers to women's full participation in the economic, political, and social arenas. The research will analyze how constitutional and legal reforms can advance gender balance rights in Nigeria by learning from Uganda, a country that is attributed with remarkable achievements in gender inclusivity. This study employed a doctrinal method utilising a comparative approach that analyzed primary legal documents, policies, and secondary sources between the two countries for the best practices and challenges. Findings reveal that Uganda's deliberate constitutional recognition of gender equity, affirmative action policies, and strong institutional frameworks have reduced gender disparity significantly. On the other hand, it is Nigeria's fragmented and under-enforced gender-related laws, and the non-express constitutional provision of gender equal participation contribute to continued inequalities. The study recommends extensive constitutional amendments, the establishment of gender-monitoring institutions, and raising awareness amongst the public in Nigeria to duplicate Uganda's successes in making gender balance a core national development agenda.